Badische Anilin- & Soda-Fabrik 2 Pfennig Gutschein (Badische Anilin- & Soda-Fabrik, 1918)
This two Pfennig Gutschein, or voucher, was issued by Badische Anilin- & Soda-Fabrik. Styled after a banknote, the verso of this company scrip includes the terms of the scrip. During World War One, paper money was issued due to the shortage of coins as metal was commonly used for the war effort. This particular voucher was issued by the Ammoniakwerk Merseburg Leuna-werk, or the ammonia works of Merseburg. Paper features a watermark design. As the first fully integrated chemical company in the world, Badische Anilin- & Soda-Fabrik was the world's largest chemical company by the the turn of the twentieth century. Merseburg, Germany was the location of Badische Anilin- & Soda-Fabrik's ammonia plant, which also produced syngas, methanol, amines, detergents and catalysts.
Keywords: Currency question; Chemical industry; Badische Anilin- & Soda-Fabrik; Corporations; Ammonia industry; Bauman, Robert Joel